Sleep duration and risk markers for type 2 diabetes: a cross-sectional study in children aged 9–10 years. (13th November 2015) - Rudnicka, Alicja R; Nightingale, Claire M; Donin, Angela S; Sattar, Naveed; Owen, Christopher G; Cook, Derek G; Whincup, Peter H
Abstract: Background: Shorter sleep duration has been associated with obesity, increased cardiovascular morbidity, and mortality in adults and with obesity in children. However, effects on childhood risk markers for cardiometabolic disease have been little studied. We examined associations between self-reported sleep duration and cardiometabolic risk markers in children and whether sleep duration might explain ethnic differences in insulin resistance. Methods: This was a cross-sectional study of 4560 children aged 9–10 years, predominantly of white European, South Asian, and black African origin, from 200 UK primary schools. Children were asked to recall usual time of going to sleep and awakening on a school day. Fasting blood samples provided concentrations of serum insulin, plasma glucose, HbA1c, and serum lipids. Physical measures included height, weight, bioimpedance, and blood pressures. Multilevel linear regression models examined the association of sleep duration (in hours) with blood markers and anthropometric measures, adjusted for sex, age quartiles, month, ethnicity, socioeconomic status, observer (physical measures only), and random effect for school; percentange changes are given for log transformed outcomes. Informed consent was obtained from parents or children, and ethics approval was given by the Multicentre Research Ethics Committee (Wales). Findings: Median sleep duration was 10·5 h (95% central range 8–12). On average, white European children slept longer than South Asian and black African children (10·4 h/night, 10·2, and 10·1, respectively). There were strong inverse graded associations between sleep duration, adiposity, and diabetes risk markers. Per hour increase in sleep duration was associated with 0·8 kg/m 3 lower ponderal index (95% CI 1·2–0·3), 0·03 kg/m 5 lower fat-mass index (0·05–0·0), 1·73% lower HOMA (homoeostatis model assessment) insulin resistance (0·50–3·91), 2·43% lower fasting glucose (0·86–3·97), and 0·19% lower HbA1c (0·0–0·39) after adjustment. Associations with diabetes risk markers remained after adjustment for adiposity and objective measures of physical activity. Sleep duration did not account for ethnic differences in insulin resistance, and was unrelated to blood pressure and serum lipids. Interpretation: The inverse association between type 2 diabetes risk markers and sleep duration in childhood is novel. Intervention studies are needed to establish causal associations, especially since increased sleep duration might offer a strategy for early prevention of type 2 diabetes. Funding: This research was supported by the National Institute for Health Research (NIHR) Collaboration for Leadership in Applied Health Research and Care (South London) and by grants from Diabetes UK and the Wellcome Trust.